UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK (PJBL) SISWA KELAS V SDS AS-SALAAM KABUPATEN TANGERANG - Nurul Fazriah; Een Unaenah; Candra Puspita Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to revitalize mathematics learning in the classroom through the implementation of Project-Based Learning (PjBL). The subjects were fifth-grade students at SDS As-Salaam, Tangerang Regency. The research was motivated by low achievement levels, as only 40% of students had reached the Minimum Mastery Criteria (KKM) score of 70, largely due to teacher-centered instruction. To address this issue, the researcher conducted a Classroom Action Research (CAR) over two cycles, each consisting of two sessions that integrated creativity, exploration, and reflection. Twenty-five students actively participated in problem-solving and project activities focused on plane geometry. Data were collected through multiple-choice tests and observations of teacher and student activities. The results showed a significant improvement, with the average student score rising from 60.7 in Cycle I to 90 in Cycle II. The classroom atmosphere also shifted toward active and collaborative learning. These findings demonstrate that PjBL is not merely a method but a mindset that enhances achievement while fostering enthusiasm and meaningful engagement in mathematics learning.